Characterization of Necroptosis-Related Molecular Subtypes and Therapeutic Response in Lung Adenocarcinoma - Zhang, Jingchen; He, Xujian; Hu, Jia; Li, Tong (Frontiers in Genetics, 2022)
Lung adenocarcinoma (LUAD) is one of the most common malignant tumors with high morbidity and mortality and usually associated with therapeutic resistance and poor prognosis due to individual biological heterogeneity. There is an unmet need to screen for reliable parameters, especially immunotherapy-related biomarkers to pre-dict patient’s outcomes. Necroptosis is a special caspase-independent form of necrot-ic cell death associated with the pathogenesis, progression and prognosis of multiple tumors but the potential connection of necroptosis-related genes (NRGs) and LUAD still remains unclear. In this study, we expounded the mutational and transcriptional alterations of 67 NRGs in 522 LUAD samples and proposed a consensus-clustering subtype of these patients into two cohorts with distinct immunological and clinical prognosis characteristics. The Cluster B patients were associated with better progno-sis and characterized by relatively lower expression of NRGs, higher immune scores in tumor microenvironment (TME), more mild clinical stages and down-regulated expression of immunotherapy checkpoints. Subsequently, the NRG score was further established to predict the overall survival (OS) of LUAD patients using univariate COX, LASSO and multivariate Cox regression analysis. The immunological charac-teristics and potential predictive capability of NRG scores were further validated by 583 LUAD patients in external datasets. Besides with better survival and immune-activated conditions, low NRG-score cohorts exhibited significant positive-correlation with the mRNA stem index (mRNAsi) and tumor mutation burden (TMB) levels. Combined with classical clinical characteristics and NRG scores, we success-fully defined a novel necroptosis-related nomogram to accurately predict the 1/3/5-year survival rate of individual LUAD patients and the potential predictive capability was further estimated and validated in multiple test datasets with high AUC value. Integrated transcriptomic analysis helps us seek for vital NRGs and supplements a novel clinical application of NRG scores in predicting the overall survival and thera-peutic benefits for LUAD patients.